Effect of Poly-Herbal Mixture Supplementation during Post partum Period on Reproductive Performance of Sahiwal Cows - Kuri, Piyali; Kumar, Parveen; Kumar, Nishant; Aggarwal, Anjali; Singh, Mahendra (Indian Journal of Animal Nutrition, 2019)
The objective of this study was to investigate effect of poly-herbal mixture supplementation in improvement of reproductive parameters in Sahiwal cows. Twelve Sahiwal cows at peri-parturient period were selected and classified into two groups (n=6) as control and supplemented (Poly-herbal mixture) on the basis of body weight, parity and expected producing ability. Control group was fed basal diet alone and in supplemented group along with basal diet, 450.025 gm poly-herbal mixture per animal was supplemented from day of calving up to 7 days continuously, then on alternate day up to day 21 and then at weekly interval up to day 60. The reproductive parameters studied during the experiment were incidence of metritis, involution status of cervix and uterus, interval from calving to 1st observed estrus, service period, number of insemination per conception and 1st service conception rate. The results showed no cases of RFM and metritis in supplemented group of cow and rapid rate of cervix and uterine involution in supplemented group compared to control. Among reproductive performance indicators, a significant (p<0.05) reduction in interval from calving to 1st observed estrus, number of services per conception and service period was found and significant (p<0.05) increase in first service conception rate was observed in cows of poly-herbal mixture supplemented group as compared to cows of control group. It was concluded that poly-herbal mixture supplementation in diet of Sahiwal cattle results in significant improvement in post partum reproductive performance.